2015
DOI: 10.1021/acs.langmuir.5b02756
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal Latex Effect on Spin-Coated Thin Conductive Polymer–Single-Walled Carbon Nanotube Layers

Abstract: We synthesize two differently sized poly(methyl methacrylate-co-tert-butyl acrylate) latexes by emulsion polymerization and mix these with a sonicated single-walled carbon nanotube (SWCNT) dispersion, in order to prepare 3% SWCNT composite mixtures. We spin-coat these mixtures at various spin-speed rates and spin times over a glass substrate, producing a thin, transparent, solid, conductive layer. Keeping the amount of SWCNTs constant, we vary the weight fraction of our smaller 30-nm latex particles relative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
(53 reference statements)
2
11
0
Order By: Relevance
“…[3][4][5][6] The underlying assumption in many of these studies is that the filler particles are oriented isotropically, which in practice need not be the case due to, e.g., processing or confinement in a thin film. [1, 17,18] In fact, we expect the percolation threshold to be close to the critical concentration at which long rod-like particles spontaneously form a nematic liquid crystal in an isotropic host fluid. [19,20] At high enough packing fraction, the particles in the isotropic phase run out of space due to excluded volume interactions and align along a common axis, i.e., the uniaxial nematic phase becomes the stable phase.…”
Section: Introductionmentioning
confidence: 89%
“…[3][4][5][6] The underlying assumption in many of these studies is that the filler particles are oriented isotropically, which in practice need not be the case due to, e.g., processing or confinement in a thin film. [1, 17,18] In fact, we expect the percolation threshold to be close to the critical concentration at which long rod-like particles spontaneously form a nematic liquid crystal in an isotropic host fluid. [19,20] At high enough packing fraction, the particles in the isotropic phase run out of space due to excluded volume interactions and align along a common axis, i.e., the uniaxial nematic phase becomes the stable phase.…”
Section: Introductionmentioning
confidence: 89%
“…If the liquid is not allowed to relax before solidification, the aligned structure is then frozen in in the final composite. [11,66,67] An often undesired effect of particle alignment is that it typically raises the percolation threshold by decreasing the contact volume of particle pairs and increasing the average surface-to-surface distance. [11,19,23,30,62,[68][69][70][71][72] In a recent study, we have theoretically shown that percolation becomes very unusual if nanoparticles align by transitioning into the uniaxial nematic phase.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, film homogeneity and film thickness need to be controlled to produce conductive polymer films. 19 To test the impact of film thickness and composition, we deposited various films using both dip coating and tested how the composition of the polymer, as well as the film thickness impacted deposition properties, and eventually sensor performance. As indicated in Supporting Information (SI) Table S2, 0.25 and 0.55 wt % poly(1-vinylpyrrolidone- co -vinyl-acetate) dip-coated samples resulted in film thickness of 35 and 53 nm, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%